Motherhood and fatherhood of parents with intellectual disabilities (review) - O. A. Rusakovskaya; G. P. Kostjuk; S. A. Golubev; L. L. Drykina; A. O. Galkina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The paper presents an overview of foreign research findings concerning parents with learning disabilities and their children. The extent of such parents in general population and among families, involved into court samples and child protection services, is presented. A review shows that parental competence is not directly related to IQ, but is mediated by additional risk factors, such as social isolation, parental stress, poverty, low socioeconomic status, poor health, poor parental childhood experience of abuse and neglect, that may be compensated by special social support. The problems of discrimination of parents with learning difficulties and necessity of their social support are discussed.